TAHAP KESEDARAN BELIA MENGIKUTI KURSUS PENDEK POGRAM PEMBELAJARAN SEPANJANG HAYAT (PSH) DI DAERAH BATU PAHAT - Sarpan, Samihah; Mohamad, Marlina (Online Journal for TVET Practitioners, 2017)
Community Colleges have been offering short courses for local community to gain knowledge, improve skills and economic income. Youths are defined those between the ages of 15 and 40, are the sources of human capital and the main pillars of a country. Therefore, this study is conducted to identify the level of youth awareness in short courses, identifying the purpose of the youths to attend short courses and identifying obstacles for the youths to short courses in life-long learning program (LLL). The design of this study was a descriptive type of survey using questionnaire forms and distributed to 384 youths in the Batu Pahat District where the items used had gained the reliability value (Alpha Cronbach) as high as 0.837. The data were analyzed quantitatively using the Statistical Packages for Social Science (SPSS) version 22.0 to get the percentage, the mean score and the T test. The findings showed that the level of youth awareness was moderate and the youth's intentions to follow the LLL short courses were to increase self-motivation and to improve self-confidence. The obstacle for the youths to attend LLL short courses is time constraint. In addition, the findings also show that there is no difference in the level of awareness in attending LLL short courses based on gender. Therefore, it is recommended that the Department of Community College of Education be able to offer more part-time, short-term programs and increase program offerings from all agencies involved